Erratum: A hierarchical multilevel Markov chain Monte Carlo algorithm with applications to uncertainty quantification in subsurface flow - Dodwell, Tim; Ketelsen, C.; Scheichl, Robert; Teckentrup, A. L. (SIAM ASA journal on uncertainty quantification, 2019)
The purpose of this erratum is to correct the statements of Lemmas 4.6 and 4.7, as well as some minor mistakes in the original publication [SIAM/ASA J. Uncertain. Quantif., 3 (2015), pp. 1075--1108].